Development of a Deep Learning Pedagogical and Ecopedagogy-Based Fundamental Movement Learning Model for Post-Disaster Physical and Psychosocial Recovery of Elementary School Students - Mudayat Mudayat (Yayasan Darussalam Bengkulu, 2026)
Indonesia's high disaster vulnerability significantly impacts elementary school students' physical and psychosocial well-being. Post-disaster, children often experience declines in physical fitness, fundamental movement skills, anxiety, and social interaction—directly affecting their learning readiness. This study aimed to develop and examine the effectiveness of a Deep Learning Pedagogical and Ecopedagogy-Based Fundamental Movement Learning Model (DL-Eco Model) as a holistic recovery intervention for post-disaster elementary school students. Employing a Research and Development (R&D) design with the ADDIE framework, the model was developed through systematic analysis, design, development, implementation, and evaluation stages. Effectiveness was tested using a quasi-experimental nonequivalent control group design across four elementary schools in one disaster-affected province (n ≈ 120 students, grades IV–V). Instruments included the Fundamental Movement Skills (FMS) test, the Indonesian Physical Fitness Test (TKJI), the Child Resilience Scale, and the Psychosocial Well-being Scale. Content validity was established using Aiken's V (≥ 0.80), and data were analyzed through descriptive and inferential statistics (independent t-test, ANCOVA, Cohen's d, and N-Gain). The DL-Eco Model integrates four instructional phases: experience orientation, movement exploration, meaningful reflection, and ecological action. This integration simultaneously addresses motor competence, reflective learning, social development, and ecological awareness—filling a conceptual and methodological gap in disaster-responsive physical education. The model is expected to contribute to the advancement of disaster-responsive pedagogy and broaden Physical Education's role as a school-based holistic recovery instrument.